PROBLEMATIKA PENERAPAN BERBICARA BAHASA ARAB DI PONDOK PESANTREN DAARUL KHAIR KOTABUMI - fuad, fathurrahman; Siddikoh, Maila; Sholehah, Mar’atus; Yanti, Sumira (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
As a separate scientific discipline, Arabic has a unique system and structure. Learning Arabic is the same as learning any other foreign language. In other words, the goal is to practice the following skills: listening, speaking, reading, and writing. The author's observations at the Daarul Khair Kotabumi Islamic Boarding School on November 1, 2023, were that there were many serious problems in learning Arabic, including the education of Santri and Daarul Khair, not MI elementary school. In public schools, it is difficult to fill Arabic classes with a language they have never studied before, so students have difficulty translating, remembering, and speaking Arabic while learning it. The research method used in this research is qualitative descriptive research using a phenomenological approach. 1. Student problems A. Students' lack of understanding of what the teacher is saying; b. Lack of student interest in learning 2. Teacher problems in learning Arabic a. Lack of teacher knowledge in the classroom and student leadership; b. The implementation of administrative functions between individuals in madrasah organizations has not been distributed optimally. The problem with learning Muhadatsah is that not all students can speak Arabic due to a lack of self-confidence and ignorance of the students' current vocabulary, because it is difficult for students to understand words well. Students' lack of knowledge in the use of current materials and structures prevents them from understanding muhadacha and vocabulary. As a result, there is no way to speak Arabic.